The use of linear programming approach in diet optimization among children under five: a scoping review - Miow, Yee Xuen; Mok, Wilfred Kok Hoe; Gan, Wan Ying; Lim, Poh Ying; Appannah, Geeta; Adznam, Siti Nur ‘Asyura (BioMed Central, 2025)
Background: Adequate nutrition is crucial for optimal child growth and development, especially for children under five. Over the years, the linear programming (LP) approach has been used to develop food-based recommendations (FBRs) for children under five. Objective: This scoping review aims to (i) summarize the use of LP in diet optimization to improve nutrient adequacy, (ii) evaluate nutrient requirements by using modelling techniques when the use of local foods is optimized, and (iii) identify and compare the problem nutrient(s). Methods: This scoping review was performed by searching PubMed and Wiley databases from 2012 to 2025, and also screened the reference lists of included publications to identify potentially eligible articles. Forward and backward citation searches were also performed to supplement the structured searches in the databases. Results: Fourteen studies were included after a systematic literature search. The objective functions and the final set of FBRs of the included studies were summarized. Moreover, the nutrient intakes in the optimized diets and the problem nutrients of the included studies were compared and discussed. When optimizing diets using the LP approach, most of the nutrient requirements can be achieved, except for iron and zinc and, in some studies, thiamine, niacin, folate, and calcium. Iron was identified as the problem nutrient in all studies involving infants aged 6 to 11 months old, followed by calcium and zinc. In children aged 12 to 23 months, iron and calcium were identified as the problem nutrients in almost all studies, followed by zinc and folate. In children aged 1 to 3 years, fat, calcium, iron, and zinc were recognized as the absolute problem nutrients, while fat, calcium, and zinc were the absolute problem nutrients for children aged 4 to 5 years. Findings on dietary inadequacy of nutrient intakes were remarkably consistent across studies conducted in different geographic and socioeconomic settings. Conclusions: Modeled diets involving local foods are inadequate to meet the requirements for certain micronutrients, particularly iron and zinc. Cost-effective strategies are required to improve the dietary adequacy of young children.